2000
DOI: 10.1046/j.1365-2265.2000.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous melatonin on catecholamine levels in postmenopausal women prior and during oestradiol replacement

Abstract: Melatonin does not modulate adrenergic activity in postmenopausal women without hormone replacement therapy. Oestradiol replacement restores the capability of melatonin to modulate adrenergic activity, particularly the norepinephrine response to stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Arangino and co-workers [24] showed that a single administration of 1 mg melatonin administration in healthy male subjects between 2:30 and 5:30 PM reduced BP, norepinephrine levels, and pulsatility index in the internal carotid artery (PI; as measure of vascular reactivity) compared to placebo administration. Cagnacci and co-workers [103] showed a reduction of systolic and diastolic BP and PI by a single daytime melatonin dose also in menopausal women with hormonal replacement therapy. However, a potential concern with daytime melatonin administration is that melatonin induces sleepiness, which most likely is an unwanted side-effect in the treatment of high BP or HR.…”
Section: The Cardiovascular System and Melatoninmentioning
confidence: 99%
“…Arangino and co-workers [24] showed that a single administration of 1 mg melatonin administration in healthy male subjects between 2:30 and 5:30 PM reduced BP, norepinephrine levels, and pulsatility index in the internal carotid artery (PI; as measure of vascular reactivity) compared to placebo administration. Cagnacci and co-workers [103] showed a reduction of systolic and diastolic BP and PI by a single daytime melatonin dose also in menopausal women with hormonal replacement therapy. However, a potential concern with daytime melatonin administration is that melatonin induces sleepiness, which most likely is an unwanted side-effect in the treatment of high BP or HR.…”
Section: The Cardiovascular System and Melatoninmentioning
confidence: 99%
“…Also a marker of bone formation such as serum bone alkaline phosphatase activity, as well as serum phosphorus levels, augmented in melatonin‐treated rats at an early time after ovariectomy [12]. As appropriate circulating oestradiol levels could be needed for melatonin effects on bone, as they are for some biological responses to melatonin in women [13], the present study was undertaken to assess whether oestradiol replacement in ovariectomized rats prolongs the response to melatonin after ovariectomy. Recently, two publications in abstract form also provided evidence on the preventing effect of melatonin on bone loss [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Whether a similar differential modulation of melatonin receptors by HRT is operative also in postmenopausal women is presently unknown. On the other hand, we have recently reported that the capability of melatonin to influence noradrenergic activity in humans is modulated by gonadal steroids: HRT allows the maximal inhibitory effect of melatonin on basal and stimulated norepinephrine levels (Cagnacci et al . 2000).…”
Section: Discussionmentioning
confidence: 99%